Fischler reflects on the need for targeted initiatives - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
The EU Agriculture Commissioner, Franz Fischler, in a speech in Alpbach,...